Klotho revisited: tubular heterogeneity reshapes mineral metabolism, aging, and CKD - Ganesh Pathare (Pflügers Archiv - European Journal of Physiology, 2026)
α-Klotho (hereafter Klotho) was discovered as an aging-suppressor protein whose function is intrinsically dependent on the kidney. Its shed ectodomain, soluble Klotho (sKlotho), is detectable in blood and urine. As an obligate co-receptor for endocrine fibroblast growth factor 23, Klotho operates at the intersection of mineral metabolism and chronic kidney disease (CKD). Within the kidney, Klotho expression is moderate in the proximal tubule but strongly enriched in the distal nephron, although the functional significance of this heterogeneity remains unclear. Recent findings from nephron segment-specific Klotho knockout mice reveal functional specialization of tubular Klotho along the nephron. According to the revised model, distal nephron Klotho regulates calcium reabsorption, bone remodeling, and urinary sKlotho levels. By contrast, proximal tubular Klotho regulates phosphate and vitamin D metabolism and is likely the principal source of circulating sKlotho; its loss recapitulates hyperphosphatemia, FGF23 resistance, and ageing-like phenotypes. This review re-evaluates the long-standing paradigm of renal Klotho biology in light of emerging evidence for functionally distinct proximal and distal nephron Klotho. Together, these insights place the kidney and its tubular Klotho heterogeneity at the center of mineral metabolism, aging and CKD.

Acute regulated expression of pendrin in human urinary exosomes - Ganesh Pathare; Nasser Dhayat; Nilufar Mohebbi; Carsten A. Wagner; Lydie Cheval; Thomas J. Neuhaus; Daniel G. Fuster (Pflügers Archiv - European Journal of Physiology, 2018)

Regulation of mineral metabolism by lithium - Hajar Fakhri; Ganesh Pathare; Abul Fajol; Bingbing Zhang; Thomas Bock; Reinhard Kandolf; Erwin Schleicher; Jürg Biber; Michael Föller; Undine E. Lang; Florian Lang (Pflügers Archiv - European Journal of Physiology, 2014)

SGK1-dependent stimulation of intestinal SGLT1 activity by vitamin D - Rexhep Rexhepaj; Ioana Alesutan; Shuchen Gu; Lisann Pelzl; Melanie Eichenmüller; Ganesh Pathare; Michael Föller; Dietmar Kuhl; Florian Lang (Pflügers Archiv - European Journal of Physiology, 2011)

Hypothyroidism of gene-targeted mice lacking Kcnq1 - Henning Fröhlich; Krishna M. Boini; Guiscard Seebohm; Nathalie Strutz-Seebohm; Oana N. Ureche; Michael Föller; Melanie Eichenmüller; Ekaterina Shumilina; Ganesh Pathare; Anurag Kumar Singh; Ursula Seidler; Karl E. Pfeifer; et al. (Pflügers Archiv - European Journal of Physiology, 2011)